PKM PEMBERDAYAAN USAHA PRODUK PANGAN KELOMPOK WANITA TANI (KWT) “MAWAR LANGGENG SARI” DESA PENGLIPURAN - I Gst B. Ngr. P. Putra; Anak Agung Ketut Jayawarsa; Ida Ayu Dinda Priyanka Maharani (Jurnal Lentera Widya, 2023)
Geographical conditions and natural conditions with cool climates are supporting factors for the ease of cultivating various types of plants in Penglipuran Village. The abundant supply of plants is utilized by the surrounding community to produce various kinds of food products. Utilization of this plant is able to produce a variety of processed products that are able to provide economic value. The processed products with natural potential include VCO (Virgin Coconut Oil) oil, jams with various flavors (pineapple, pumpkin and rosella), to various dry spices (ginger and turmeric). To increase interest from consumers, the resulting product has been properly packaged. This product is produced and marketed under the Kelompok Wanita Tani "Mawar Langgeng Sari" chaired by Nengah Artawati. The problems faced by partners include: 1) Partners experience problems in the process of recording product sales transactions. This business group often experiences difficulties in determining the right cash inflows and outflows. In addition, the bookkeeping process is still carried out conventionally so it is less effective and efficient; 2) The distribution and marketing of products is still carried out in a traditional way, resulting in a very minimal coverage of product market share; 3) The facilities and infrastructure used have expired, so they require renewal so that they can provide better benefits in the future. The solutions offered for this problem are 1) Training for Recording Financial Transactions and Provision of a Digitalized Financial Recording System; 2) Provision of a Website as a Form of Online Marketing Strategy and Marketing Strategy Training (Via Third Party Applications); 3) Provision of Production Supporting Facilities and Infrastructure.